Cost-effective maintenance of railway track proceedings of the conference Cost-effective maintenance of railway track organized by the Institution of Civil Engineers and held in London on 25-26 June 1992. (Thomas Telford, 1992)
Shows how railways can be kept running using the minimum necessary maintenance, taking into account the environmental conditions and the type and volume of traffic using the railway. This volume includes: a discussion on the choice of materials that are appropriate to the environment of the railway, and advice from the industrialized countries.